2022
DOI: 10.1177/09544089221087819
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis and experimental investigation of moving heat source model for GMAW deposited mild steel weld bead

Abstract: An investigation has been done to identify the heat source model suitable for numerical modeling of the Gas Metal arc Welding (GMAW) welding process. In the present investigation, a numerical model was constructed to simulate the GMAW welding process through transient thermal analysis for different thermal heat source models for weld deposition of Mild steel considering semi-cylindrical weld bead geometry. The Gaussian heat source with radial coordinate system and double ellipsoidal thermal heat source have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…It was concluded that content of carbon in IS 2062 steel had a significant effect on weldability. Aslam and Sahoo (2022) observed coarse grain structure in HAZ and grain structure with fine columnar nature at penetration and weld bead region. Arunkumar et al.…”
Section: Introductionmentioning
confidence: 96%
“…It was concluded that content of carbon in IS 2062 steel had a significant effect on weldability. Aslam and Sahoo (2022) observed coarse grain structure in HAZ and grain structure with fine columnar nature at penetration and weld bead region. Arunkumar et al.…”
Section: Introductionmentioning
confidence: 96%
“…Conventional welding techniques such as shielded metal arc welding, gas tungsten arc welding, gas metal arc welding (GMAW) and submerged arc welding are widely used for joining the BSK 46 steels. [9][10][11][12][13][14][15][16][17][18] GMAW is preferred over the other arc welding processes because of its cost-effectiveness, higher filling rate, relatively easy to operate and higher productivity. [19][20][21][22][23][24] In GMAW, the arc generated between the workpiece and wire electrode melts the workpiece and produces a permanent joint.…”
Section: Introductionmentioning
confidence: 99%
“…In this sophisticated welding technique, a pair of heat sources work in tandem to regulate the thermal input within the weld zone. One potential heat source might be the gas metal arc welding (GMAW) process, employed in the spray-transfer mode, which bolsters the consistency of chemical composition while mitigating issues associated with distortion during welding [ 3 , 4 , 5 ]. A more gradual cooling pace within the critical transformation domain permits the hybrid laser-arc welding (HLAW) method to amalgamate a profound weld-penetration depth with a low power consumption innate to laser welding, thereby achieving heightened energy efficiency and metallurgical stability [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%